C/EBPα is required for differentiation of white, but not brown, adipose tissue - Linhart, Heinz G. (The National Academy of Sciences, 2001)
The transcription factor CCAAT enhancer binding protein α (C/EBPα) is expressed at high levels in liver and adipose tissue. Cell culture studies show that C/EBPα is sufficient to trigger differentiation of preadipocytes into mature adipocytes, suggesting a central role for C/EBPα in the development of adipose tissue. C/EBPα knockout mice die within 7–12 h after birth. Defective gluconeogenesis of the liver and subsequent hypoglycemia contribute to the early death of these animals. This short life span impairs investigation of the development of adipose tissue in these mice. To improve the survival of C/EBPα−/− animals, we generated a transgenic line that expresses C/EBPα under the control of the albumin enhancer/promoter. This line was bred into the knockout strain to generate animals that express C/EBPα in the liver but in no other tissue. The presence of the transgene improved survival of C/EBPα−/− animals almost 3-fold. Transgenic C/EBPα−/− animals at 7 days of age show an absence of s.c., perirenal, and epididymal white fat despite excess lipid substrate in the serum, whereas brown adipose tissue is somewhat hypertrophied and shows minimal biochemical alterations. Interestingly, mammary gland fat tissue is present and exhibits normal morphology. The absence of white adipose tissue in many depots in the presence of high serum lipid levels shows that C/EBPα is required for the in vivo development of this tissue. In contrast, brown adipose tissue differentiation is independent of C/EBPα expression. The presence of lipid in brown adipose tissue serves as an internal nutritional control, indicating that neither nutritional intake nor lipoprotein composition is likely responsible for the absence of white fat.